Seven steps to resolve conflicts (Journal of Parents and Teachers, 2023)
The article mentions some steps we can follow to resolve conflicts in general. It starts with the approach of them and values what we can learn. Finally it also gives some tips to find solutions.
Keywords: steps; conflicts; resolve